Effects of Highly Active Antiretroviral Therapy (HAART), on Some Micronutrients in HIV Positive Patients at Nsukka - Obiageli, Aniagolu Miriam (International Journal For Research In Health Sciences And Nursing, 2016)
Some biological changes are observed during human immuno deficiency virus infection. Once CD4+ count decreases to 500 cells/mm3 highly active antiretroviral therapy (HAART) is initiated.This work, seeks to elucidate the effect of HAART on some of the biochemical changes caused by HIV infection. 63 subjects comprising, 20 apparently healthy control subjects and 43 HIV positive subjects ready to be placed on HAART were recruited for the study. Concentrations of the following biochemical parameters: zinc, selenium, vitamin C, vitamin E and also CD4+ count was determined. The results showed that CD4+ count increased significantly from baseline to 8 months into treatment (p < 0.05), zinc and selenium increased significantly from baseline to 8 months into treatment, but vitamin C increased up to the 4th month but deteriorated by the 8th month of initiation into HAART. Vitamin E showed no significant change in concentration (p > 0.05). There were significant positive correlations between the mean CD4+ count and the mean concentrations of zinc (p < 0.05). In this study, only zinc was significantly positively correlated with CD4+ count.